MEASURING AND ANALYZING THE RELATIONSHIP BETWEEN FINANCIAL INCLUSION AND BANK DEPOSITS IN IRAQ (World Economics and Finance Bulletin, 2024)
The research highlights the measurement and analysis of the dynamic interactions (short-term and long-term) between some financial inclusion indicators (number of bank branches, ATM machines, credit extended to the private sector, broad money supply) as independent variables, and bank deposits as a dependent variable, using the ARDL model. Additionally, quarterly data covering the period (2010-2023) were used. The research assumes that there is both a negative and positive effect of certain financial inclusion indicators on bank deposits in Iraq. Finally, the results of the dynamic interactions revealed that the two indicators (number of bank branches and credit extended to the private sector) have a positive impact on bank deposits in the short term, but they have a negative impact in the long term. As for the two indicators (ATM machines and broad money supply), they have a negative and positive effect on bank deposits in the short term due to time lags, but in the long term, the ATM indicator has a negative impact on bank deposits, while the broad money supply indicator has a positive effect. Therefore, policymakers in the Iraqi financial sector should focus on improving financial infrastructure, raising financial awareness among individuals and institutions, encouraging innovation in financial services, and enhancing the stability of the financial system in order to promote financial inclusion and increase bank deposits, which will contribute to sustainable economic development in Iraq
Keywords: Some financial inclusion indicators; bank deposits